Writing development in children with hearing loss, dyslexia, or oral language problems : implications for assessment and instruction - Arfé, Barbara (Oxford University Press, 2014)
Writing is challenging for the majority of learners. For students with language problems, difficulties with written expression are considered one of the most common learning challenges. There is much to learn about the ways in which oral language skills impact on the acquisition of written language in children. Writing Development in Children with Hearing Loss, Dyslexia, or Oral Language Problems focuses on the nature of the writing problems experienced by children with oral language problems. Three clinical groups are considered: children with hearing loss, oral language difficulties, and dys.